Finance and economy for society : integrating sustainability - Alijani, Sharam; Karyotis, Catherine (Critical studies on corporate responsibility, governance and sustainability ;, 2016)
Critical Studies on Corporate Responsibility, Governance and Sustainability examines the social, economic and environmental impacts of corporations, and the real effects of corporate governance, CSR and business sustainability on societies in different regions. It facilitates a better understanding of how value systems, cultures and traditions in different societies may affect the policies and practices of corporate responsibility, governance and sustainability. The latest volume in the series identifies the future development trends of corporate responsibility, governance and sustainability in contexts when examining and exploring those key issues.